An optimal algorithm for small group multicast in wireless sensor networks. (2018) - Luo, Weizhong; Wang, Jianxin; Cai, Zhaoquan; Peng, Gang; Guo, Jiong; Zhang, Shigeng
We propose an optimal algorithm to construct a delay-bounded minimum energy routing tree for multicast in wireless sensor networks. Finding the minimum energy multicast tree with constrained delay has been proved to be a NP-hard problem. Existing works mainly focus on developing approximation or heuristic algorithms to find approximate solutions. We formally define the Min-power h-Multicast problem - to find a minimum energy multicast tree in which the path from the source to every destination node is less than h hops - and translate it into a minimum Steiner tree problem. We then develop a dynamic programming algorithm to get an optimal solution to the problem with a running time that is exponential exclusively with respect to the size of the multicast group. Simulation results show that, compared with existing algorithms, our algorithm saves energy consumption by factors between 19% and 42% with comparable running time for small group multicast.